Step
*
2
2
1
2
1
of Lemma
rv-orthogonal-iff
.....assertion..... 
1. rv : InnerProductSpace
2. f : Point(rv) ⟶ Point(rv)
3. f 0 ≡ 0
4. ∀[x,y:Point(rv)].  (||f x - f y|| = ||x - y||)
5. ∀x,y:Point(rv).  (x ≡ y 
⇒ f x ≡ f y)
6. ∀x,y:Point(rv).  f x + y ≡ f x + f y
7. x : Point(rv)
8. a : ℝ
9. ∀n:ℕ. ∀x:Point(rv).  f r(n)*x ≡ r(n)*f x
⊢ ∀n:ℕ+. ∀x:Point(rv).  f (r1/r(n))*x ≡ (r1/r(n))*f x
BY
{ (Auto
   THEN (InstHyp [⌜n⌝;⌜(r1/r(n))*x1⌝] (-3)⋅ THENA Auto)
   THEN (Assert f r(n)*(r1/r(n))*x1 ≡ f x1 BY
               (BHyp 5 THEN Auto THEN (RWO  "rv-mul-mul" 0 THENM nRNorm 0) THEN Auto))) }
1
1. rv : InnerProductSpace
2. f : Point(rv) ⟶ Point(rv)
3. f 0 ≡ 0
4. ∀[x,y:Point(rv)].  (||f x - f y|| = ||x - y||)
5. ∀x,y:Point(rv).  (x ≡ y 
⇒ f x ≡ f y)
6. ∀x,y:Point(rv).  f x + y ≡ f x + f y
7. x : Point(rv)
8. a : ℝ
9. ∀n:ℕ. ∀x:Point(rv).  f r(n)*x ≡ r(n)*f x
10. n : ℕ+
11. x1 : Point(rv)
12. f r(n)*(r1/r(n))*x1 ≡ r(n)*f (r1/r(n))*x1
13. f r(n)*(r1/r(n))*x1 ≡ f x1
⊢ f (r1/r(n))*x1 ≡ (r1/r(n))*f x1
Latex:
Latex:
.....assertion..... 
1.  rv  :  InnerProductSpace
2.  f  :  Point(rv)  {}\mrightarrow{}  Point(rv)
3.  f  0  \mequiv{}  0
4.  \mforall{}[x,y:Point(rv)].    (||f  x  -  f  y||  =  ||x  -  y||)
5.  \mforall{}x,y:Point(rv).    (x  \mequiv{}  y  {}\mRightarrow{}  f  x  \mequiv{}  f  y)
6.  \mforall{}x,y:Point(rv).    f  x  +  y  \mequiv{}  f  x  +  f  y
7.  x  :  Point(rv)
8.  a  :  \mBbbR{}
9.  \mforall{}n:\mBbbN{}.  \mforall{}x:Point(rv).    f  r(n)*x  \mequiv{}  r(n)*f  x
\mvdash{}  \mforall{}n:\mBbbN{}\msupplus{}.  \mforall{}x:Point(rv).    f  (r1/r(n))*x  \mequiv{}  (r1/r(n))*f  x
By
Latex:
(Auto
  THEN  (InstHyp  [\mkleeneopen{}n\mkleeneclose{};\mkleeneopen{}(r1/r(n))*x1\mkleeneclose{}]  (-3)\mcdot{}  THENA  Auto)
  THEN  (Assert  f  r(n)*(r1/r(n))*x1  \mequiv{}  f  x1  BY
                          (BHyp  5  THEN  Auto  THEN  (RWO    "rv-mul-mul"  0  THENM  nRNorm  0)  THEN  Auto)))
Home
Index